Comparison of Energy Expenditure Observed between Scheduled Activities in Collegiate Team-Sport Female Athletes - Jessica M. Moon; Hannah A. Zabriskie; Patrick S. Harty; Bradley S. Currier; Julia C. Blumkaitis; Richard A. Stecker; Andrew Jagim; Chad M. Kerksick (MDPI AG, 2021)
Energy needs of female team-sport athletes are poorly understood with no evidence highlighting differences present between scheduled activities. The purpose of this study was to examine the difference in energy expenditure between NCAA Division II female basketball (BBALL) and lacrosse (LAX) athletes during different scheduled team activities. Female BBALL (n = 13; 19.8 ± 1.3 yrs; 173.9 ± 13.6 cm; 74.6 ± 9.1kg; 27.1 ± 3.2%fat) and LAX (n = 20; 20.4 ± 1.8yrs; 168.4 ± 6.6cm; 68.8 ± 8.9kg; 27.9 ± 3.1%fat) athletes were outfitted with heart rate and activity monitors during four consecutive days on five different occasions (20 days total) across an entire academic year to assess differences in total daily activity energy expenditure (TDEE), activity energy expenditure (AEE), and physical activity level (PAL). Data were categorized by type of scheduled daily activities: Practice, Game, Conditioning, or Off. Independent of day type, TDEE, AEE, and PAL levels were greater (p < 0.05) in BBALL athletes. For each sport, TDEE, AEE, and PAL were significantly different (p < 0.05) between classified activity days. BBALL and LAX athletes experienced higher values on game days for TDEE, AEE, and PAL, with the lowest values experienced on off days. In conclusion, calculated levels of TDEE, AEE, and PAL in female collegiate BBALL and LAX athletes were determined to be different, irrespective of the scheduled activity.